Aprender a (re)escrever: o processo de construção do habitus escritural acadêmico de alunos ingressantes do Curso de Pedagogia da UFC - Franklin, Sue Ellen Guimarães dos Santos (2023)
In this research, I analyzed the process of construction of the academic writing habitus among students entering the Pedagogy course at UFC, describing the dispositions that build this habitus concept and their assistance in the claiming of an identity as an academic writer. As the main theoretical sources, we used speeches by Vygotsky (2007; 2009) about schooling, as well as the notion of relationship with writing by Barré-de Miniac (2002; 2006), the approach to academic literacies by Lea and Street (2014 ) and Bourdieu's concepts of habitus, field and cultural capital (1993; 2001; 2004; 2008). As a methodology, traces of the ethnographic research approach and (auto)biographical research were considered, through the following data construction techniques: participant observation, balance of knowledge (Charlot, 2009) and semi-structured interviews, which were carried out with beginner students in university, both during the first semester of the course and after having already completed it. Data analysis allows us to conclude that the dispositions that helped to constitute the students' writing habitus are guided to social and power relations arising from the family and school ambience, from which they conceive writing, in the most cases, as a gift or mastery of a technique with an evaluative purpose. When arriving at the University, there is a process of reconfiguration in the dispositions incorporated throughout the students' school trajectories, which incorporates new dispositions regarding their ways of feeling, thinking and acting in relation to this social practice called academic writing. An example of these reconfigurations is that, now, in addition to grammatical rules and standards of the Portuguese language, they also need to take account of ABNT standards and base their statements on readings from the academic community itself. So, when reconstructing their academic writing habitus, students begin to relate to writing, trying to design an identity/condition as a writer in which they know how to communicate with their peers, as well as interact with the power relations present in the academic field and with the meanings attributed to writing as cultural capital in this new space of relationships that is opening up for them.